2017
DOI: 10.19183/how.24.2.338
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cognitive Styles and Young Adult Learners’ Preferences for Written Corrective Feedback

Abstract: This study aimed to investigate the relationship between learners' cognitive styles and their preferences for different types and frequencies of written corrective feedback and for different types of errors to be corrected. Data were collected from 60 English as a foreign language learners at intermediate and upper-intermediate levels. The instruments included the Ehrman and Leaver Learning Styles Questionnaire, and a questionnaire constructed by Amrhein and Nassaji (2010). The results indicated that there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…The mean responses of the perception of synoptic students revealed that this group disagree with no correction. The results were consistent with the previous studies (Ehrman & Leaver, 2003;Moslemi & Dastgoshadeh, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The mean responses of the perception of synoptic students revealed that this group disagree with no correction. The results were consistent with the previous studies (Ehrman & Leaver, 2003;Moslemi & Dastgoshadeh, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…The second question results indicated that there was a relationship between learners' cognitive styles and their preferences for different types of errors to be corrected. As similar as the first research question's findings, the findings of this research question were in line with the previous studies (Ellis, 2012;Moslemi & Dastgoshadeh, 2017;Robinson, 2002;Salih Tasdemir & Yalcin Arsalan, 2018). Robinson (2002) stated that individual factors (specifically affective and cognitive factors) as crucial factors mediate between instruction and L2 learning.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A plethora of published research has examined the relationship between students' CF preferences and backgrounds (Jolley, 2019;Morris & Chikwa, 2016;Moslemi & Dastgoshadeh, 2017;Nurie, 2018;Parkes & Fletcher, 2017;Tasdemir & Yalcin Arslan, 2018;Yang, 2016). For instance, Yang (2016) discovered that L2 learners with a Confucian cultural background considered explicit correction of pragmatic errors as effective, whereas learners from a non-Confucian background did not concur.…”
mentioning
confidence: 99%